2018
DOI: 10.1177/0825859718779455
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudes, Needs, and Requirements at End of Life in the Republic of Georgia (Comparative Analysis of Groups of Patients With Cancer and Elders)

Abstract: The attitudes, needs, and requirements at the end of life of the people are basically similar, regardless of what determined the sense of limitation of the remaining life-incurable disease or advanced age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In three studies, participants reported a strengthening of connections with family and close friends following a terminal diagnosis and a deeper sense of meaning being created between themselves and their loved ones ( Lee et al, 2013 ; Maiko et al, 2019 ; Willig, 2015 ). Participants in four further studies reported a strong need to feel connected with others and this connection provided them with an increased sense of wellbeing ( Bentur et al, 2014 ; Chikhladze et al, 2018 ; Lee and Ramaswamy, 2020 ; Peoples et al, 2018 ); in one of these studies, this was especially the case for family members, whose happiness and wellbeing were deeply connected to that of their own ( Bentur et al, 2014 ). Relationships with family and friends were also reported as being important factors in providing meaning in life for participants in two studies ( Bentur et al, 2014 ; Lee and Ramaswamy, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In three studies, participants reported a strengthening of connections with family and close friends following a terminal diagnosis and a deeper sense of meaning being created between themselves and their loved ones ( Lee et al, 2013 ; Maiko et al, 2019 ; Willig, 2015 ). Participants in four further studies reported a strong need to feel connected with others and this connection provided them with an increased sense of wellbeing ( Bentur et al, 2014 ; Chikhladze et al, 2018 ; Lee and Ramaswamy, 2020 ; Peoples et al, 2018 ); in one of these studies, this was especially the case for family members, whose happiness and wellbeing were deeply connected to that of their own ( Bentur et al, 2014 ). Relationships with family and friends were also reported as being important factors in providing meaning in life for participants in two studies ( Bentur et al, 2014 ; Lee and Ramaswamy, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“… Ellis and colleagues (2015) found that, through their suffering, participants experienced a spiritual transformation, which enabled them to gain a deeper understanding of themselves and a greater ability to cope with their illness. Transcendence, a feeling of being connected with something which is greater than oneself, was reported by participants of one study as being an important spiritual need at end of life ( Chikhladze et al, 2018 ). In another study, transcendence occurred as a transformation in the way participants connected with their family ( Hughes et al, 2015 ) and in a further study, transcendence was experienced by participants in their renewed outlook on life ( Reeve et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the lowest mean facet score was for intimacy. In a mixed comparative analysis of groups on end of life needs in terminally ill patients with cancer and older adults > 85 years, Chikhladze et al 49 described that frequently alluded themes included social relation (belonging), love, esteem, and transcendence, underscoring the importance of promoting the fulfillment of psychological needs, which are higher in the Maslow's hierarchy 50 , in older patients with cancer.…”
Section: Discussionmentioning
confidence: 99%